Molecular characterization of a recombinant managanese superoxide dismutase from Lactococcus lactis M4 - Tan, Boon Hooi; Leow, Adam Thean Chor; Foo, Hooi Ling; Abdul Rahim, Raha (Hindawi Publishing Corporation, 2014)
A superoxide dismutase (SOD) gene of Lactococcus lactis M4 was cloned and expressed in a prokaryotic system. Sequence analysis revealed an open reading frame of 621 bp which codes for 206 amino acid residues. Expression of sodA under T7 promoter exhibited a specific activity of 4967 U/mg when induced with 1 mM of isopropyl-β-D-thiogalactopyranoside. The recombinant SOD was purified to homogeneity by immobilised metal affinity chromatography and Superose 12 gel filtration chromatography. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis and western blot analyses of the recombinant SOD detected a molecular mass of approximately 27 kDa. However, the SOD was in dimer form as revealed by gel filtration chromatography. The purified recombinant enzyme had a pI of 4.5 and exhibited maximal activity at 25°C and pH 7.2. It was stable up to 45°C. The insensitivity of this lactococcal SOD to cyanide and hydrogen peroxide established that it was a MnSOD. Although it has 98% homology to SOD of L. lactis IL1403, this is the first elucidated structure of lactococcal SOD revealing active sites containing the catalytic manganese coordinated by four ligands (H-27, H-82, D-168, and H-172).